New Approaches to the Pathogencity of Fungal Diseases on Olive Leaves - AVAN, Meltem; ATAY, Mehmet (ISPEC Journal of Agricultural Sciences, 2022)
Olive is a species of Olea europaea Linnaeus belonging to the genus Olea, which is the edible fruit of the Oleaceae family in the form of a bush, which is very long-lived and does not lose its productivity throughout its life. Since olive cultivation is mostly done in the Mediterranean basin, our country has also played an important role in olive cultivation. Fungal factors that cause disease in olive production areas cause significant yield and quality losses in the plant. Diseases such as Verticillium wilt (Verticillium dahliae), Ringed spot (Spilocaea oleaginea=Cycloconium oleaginum), anthracnose (Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. (syn. Gloeosporium olivarum Alm.) It also increases in our country and causes significant problems. Since it has leaves that can be considered narrow and small due to its form, there are sometimes great difficulties in pathogenicity tests performed on the leaves of the plant in order to determine fungal agents. In this study, it is thought that this method, which was developed by placing wet cotton-wrapped shoots in jars, as an alternative to the three existing pathogenicity methods, can be considered as a suitable option in order to eliminate the existing application difficulties in pathogenicity studies.